Association between cytotoxin producing H. pylori and gastric carcinoma (Bangladesh Medical Journal Khulna, 2017)
Background: Enormous studies have been conducted worldwide regarding CagA+ status of H. pylori in gastric carcinoma Objective: No study relating CagA+ status and gastric carcinoma has been carried out in our country yet. This study has been designed to see the association between CagA+ H. pylorl strain and gastric carcinomaMethods: For this purpose, a total number of 80 (eighty) patients were selected. Of the 80 (eighty) patients, 40 (forty) were selected as cases (malignant) and the remainder 40 (forty) were selected as controls (non malignant). H. pylori was detected by applying non invasive (H. pylori IgG serology and CagA-IgG serology) and invasive (Histology and rapid urease test) technique. Of them Histology was done by Modified giemsa stain which was regarded as gold standard, CagA IgG was detected by ELISA method.Results: In this study, among the 40 cases, 35 (thirty five) possess the CagA+ H. pylori strain and among the 40 controls, 33 (thirty three) bear the CagA+ H. pylori strain. In this study, no significant difference between case and control on the point of CagA-IgG status was found.Conclusion: H.pylori may be a simple initiator and not the actual cause of gastric carcinoma.Bang Med J (Khulna) 2016; 49 : 13-17